Access and Retention of Marginalized Populations Within Undergraduate Music Education Degree Programs. (July 2014) - Fitzpatrick, Kate R.; Henninger, Jacqueline C.; Taylor, Don M.
The purpose of this collective instrumental case study was to examine the experiences of six undergraduate students from traditionally marginalized populations with regard to their preparation for, admission to, and retention within a music education degree program. Analyzed and reported through the lens of critical theory, data sources included semistructured interviews with the participants and structured interviews with their high school music teacher and a university-based mentor. Participants described a lack of resources with regard to their preparation for auditions as well as a lack of information regarding the application and audition process. Such inhibiting factors were mediated by personal initiative, hard work, and dedication. The presence of role models and mentors was considered an important aid to their retention within music education degree programs. Participants also provided suggestions for improving access, admission, and retention of students from traditionally marginalized populations.